(untitled) (Research, Society and Development, 2022)
In order to prevent COVID 19 spread it was proposed social isolation. However, strong social straining and social distance have raised negative impacts on the population, mainly about emotional and general health aspects. Objective: To analyze the impact of COVID-19 isolation on general and emotional health self-perception of Brazilians. Methodology: 660 participants took part of an online survey and the collection was carried out from August to September 2020 during the COVID-19 pandemic. The online survey was designed with 26 closed multiple-choice questions (identification data, general health and emotional aspects) by the researchers Results: The average age was 36 years, 80% were female and residents of all Brazilian states. 36.2% worked in a home office and 17.4% lost their jobs during the COVID-19 pandemic. Only 50.7% carried out social isolation. Among the emotional aspects, anxiety (p=0.083) and stress (p=0.014) were the most highlighted, therefore there were a significant change in diet (p=0.017) and the presence of tinnitus (p=0.070). The positive COVID-19 test (n=73) were significant for stress (p=0.017), presence of tinnitus (p=0.038) and dizziness (p=0.000). Conclusion: It was concluded that social isolation was a risk factor for increased stress, change in eating habits and the onset of tinnitus, in addition a greater tendency for anxiety; and COVID-19 infection was a risk factor for stress and for the onset of dizziness and tinnitus among the participants.